2017
DOI: 10.1177/1362361317708287
|View full text |Cite
|
Sign up to set email alerts
|

Perspective-taking is two-sided: Misunderstandings between people with Asperger’s syndrome and their family members

Abstract: Misunderstandings are social in nature, always having two sides. Yet the misunderstandings experienced by people with Asperger’s syndrome are usually studied in terms of the individual with a diagnosis, with less emphasis on social relations. We use a two-sided methodology to map out misunderstandings within 22 dyads (n = 44) consisting of people with Asperger’s syndrome and their family members. Both sides of the relationship were asked about 12 topics in terms of one’s rating of Self, one’s rating of Other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 73 publications
4
88
0
Order By: Relevance
“…Research concerning perspective taking among autistic adults has shown that they are able to recognize the effects of their ASD and that their family members are likely to rate ASD-related skills lower than their own self-ratings. 32 A study comparing adults' AQ with parental report of developmental history found that only 44% of adults on the spectrum scored above the cutoffs. 33 However, one study that assessed the predictive validity of two short forms of the AQ and the RAADS-R found high levels (80%) of confirmation of ASD diagnosis among adults.…”
Section: Introductionmentioning
confidence: 99%
“…Research concerning perspective taking among autistic adults has shown that they are able to recognize the effects of their ASD and that their family members are likely to rate ASD-related skills lower than their own self-ratings. 32 A study comparing adults' AQ with parental report of developmental history found that only 44% of adults on the spectrum scored above the cutoffs. 33 However, one study that assessed the predictive validity of two short forms of the AQ and the RAADS-R found high levels (80%) of confirmation of ASD diagnosis among adults.…”
Section: Introductionmentioning
confidence: 99%
“…One good example is the work of Brett Heasman at the London School of Economics. 18 I am excited about how this research can help to redefine what we mean by autism itself in the long run. What needs to be done is more such work from different disciplines coming together for that multidisciplinary effort, such as today, bringing together research in autistic people to plan ways forward, and to take on board the social context of these issues.…”
Section: Introductionmentioning
confidence: 99%
“…People often generalize inappropriately from their own behaviors to determine what counts as social or communicative behavior in others; this is an experience-based bias that constrains the ability to view others' unconventional or idiosyncratic behaviors as attempts to communicate and connect (Li & Koenig, 2019). But we should keep in mind that communication and connection are reciprocal processes; this seems obvious but tends to be ignored when one member of a dyad is autistic (Dinishak & Akhtar, 2013;Gernsbacher, 2006;Heasman & Gillespie, 2018;Milton, 2012).…”
Section: Discussionmentioning
confidence: 99%